The state of the world's plant genetic resources for food and agriculture : L'état des ressources phytogénétiques pour l'alimentation et l'agriculture dans le monde = El estado de los recursos fitogenéticos en el mundo para la alimentación y la agricultura. (Food and Agriculture Organization of the United Nations, 1997)
Prepared from 158 country reports, 15 sub-regional syntheses reports, this Global Plan of Action is the 1st comprehensive assessment effort to safeguard plant genetic resources and use them to ensure food security and sustainability of agriculture.